Possibilities and priorities for IJED in times of uncertainty: A 40th anniversary analysis. (November 2020) - Crossley, Michael; King, Kenneth; McGrath, Simon; Watson, Keith
Abstract: This article reflects upon the history of the Journal, its evolving nature and rationale and upon possibilities and priorities for the future in what are uncertain times for all.